One-pot oligoamides syntheses from l-lysine and l-tartaric acid. Issue 20 (20th February 2017) - Oliva, R.; Ortenzi, M. A.; Salvini, A.; Papacchini, A.; Giomi, D.
Abstract : Oligoamides based on natural raw materials, l -lysine andl -tartaric acid, were synthesized using one-pot processes. Al -lysine diketopiperazine structure was obtained with good selectivity without protection/deprotection steps. Abstract : Oligoamides based on natural raw materials, l -lysine andl -tartaric acid, were synthesized using one-pot processes. Anl -lysine diketopiperazine structure was obtained with good selectivity without protection/deprotection steps. Reactions were performed using two methods, the first involving the use of solvent and catalyst under a nitrogen atmosphere, the second exploiting the "raw" monomers under vacuum. The reaction products were characterized through FT-IR, NMR and MALDI spectroscopies, acid–base titration, SEC and polarimetric analyses. Thermal properties were evaluated by DSC and TGA analyses.